Effects of phytocompound Precocene 1 on the expression and functionality of the P450 gene in λ-cyhalothrin-resistant Spodoptera litura (Fab.) - Shyam-Sundar, Narayanan; Ramasubramanian, Ramakrishnan; Karthi, Sengodan; Senthil-Nathan, Sengottayan; Chanthini, Kanagaraj Muthu-Pandian; Sivanesh, Haridoss; Stanley-Raja, Vethamonickam; Ramkumar, Govindaraju; Narayanan, Kilapavoor Raman; Mahboob, Shahid; Al-Ghanim, Khalid Abdullah; Abdel-Megeed, Ahmed; et al. (Frontiers in Physiology, 2022)
Spodoptera litura (Fabricius) is a polyphagous agriculturally significant insect pest that has evolved a high level of resistance to conventional insecticides. Diet incorporation assay was used in this work to assess the resilience of field populations of S. litura to λ -cyhalothrin. Analysis of function and expression of the cytochrome p450 gene was used to test the sensitivity of S. litura larvae to the sub-lethal concentrations of insecticidal plant chemical Precocene 1 alone and in combination with λ-cyhalothrin.Activities of esterase enzymes (α and β) were found to decrease 48h post treatment with Precocene 1. The activities of GST enzyme and cytochrome p450 however, increased with Precocene 1 treatment post 48hrs. Expression studies revealed the modulation of cytochrome P450 genes, CYP4M16, CYP4M15, CYP4S8V4, CYP4G31 and CYP4L10 by Precocene 1. While CYP4M16 expression was most stimulated bythe synergistic Precocene 1 + λ –cyhalothrin treatment, expression of CYP4G31 was the most down regulated by Precocene 1 exposure. Hence it is evident that λ –cyhalothrin resistant pest populations are still sensitive to Precocene 1 at sublethal concentration that is yet capable of debarring their development. Therefore, Precocene 1 could be used as a potent candidate in the effective management of insecticide resilient S. litura.